Neratinib is effective in breast tumors bearing both amplification and mutation of ERBB2 (HER2) - Cocco, Emiliano (Sci Signal, 2018)
Mutations in the gene encoding epidermal growth factor receptor (EGFR) family member HER2 (ERBB2) are common in and drive the growth of “HER2-negative” (not ERBB2-amplified) solid tumors but are rare in primary “HER2-positive” (ERBB2-amplified) breast cancer. We analyzed DNA sequencing data from HER2-positive patients and used cell lines and a patient-derived xenograft model to test the effects of HER2 mutations on the efficacy of anti-HER2 agents such as trastuzumab, lapatinib, or the irreversible pan-EGFR inhibitor neratinib. HER2 mutations were present in ~ 7% of HER2-positive tumors, all of which were metastatic but not all were previously treated. Compared to HER2-amplification alone, in both patients and cultured cell lines, co-occurrence of HER2 mutation and amplification was associated with poor response to trastuzumab and lapatinib, standard-of-care anti-HER2 agents. In mice, xenografts established from a patient whose HER2-positive tumor acquired a D769Y mutation in HER2 after progression on trastuzumab-based therapy were resistant to trastuzumab or lapatinib but were sensitive to neratinib. Clinical data revealed that six heavily pretreated patients with tumors bearing coincident HER2 amplification and mutation subsequently exhibited significant response to neratinib monotherapy. Thus, the findings indicate that coincident HER2 mutation reduces the efficacy of therapies commonly used to treat HER2-positive breast cancer, particularly in metastatic and previously HER2-inhibitor–treated patients as well as potentially in patients scheduled for first-line treatment. We propose, therefore, that clinical studies testing the efficacy of neratinib are warranted selectively in breast cancer patients whose tumors carry both amplification and mutation of HER2/ERBB2.